(3JPcQI Gdedhc Edi CMSf GdSdhcs - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG dOjf GdESdGe s
(3CdagG HYV GdCaGVd HQSe Gdedc GdCTQa CHj GdfUQ bGfUhg GdZhQi hQJHgG Ydi CQHYI CHhGHs
(3fSNI eUhQI YZf fSNI CjG hUajG HGdBSJGfg Qbe (B4144s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B308s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B87 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs